Limited Effect of Perioperative Systemic Therapy in Patients Selected for Repeat Local Treatment of Recurrent Colorectal Cancer Liver Metastases - Tessa Hellingman, MD, MSc; Boris Galjart, MD; Julia J. Henneman, MD; Burak Görgec, MD; Okker D. Bijlstra, MD; Martijn R. Meijerink, MD, PhD; Alexander L. Vahrmeijer, MD, PhD; Dirk J. Grünhagen, MD, PhD; Hans J. van der Vliet, MD, PhD; Rutger-Jan Swijnenburg, MD, PhD; Cornelis Verhoef, MD, PhD; Geert Kazemier, MD, PhD (Annals of Surgery Open, 2022)
Objectives:. The aim of this study was to determine the potential benefit of perioperative systemic therapy on overall and progression-free survival after repeat local treatment in patients suffering from recurrent colorectal cancer liver metastasis (CRLM). Background:. The optimal treatment strategy in patients with recurrent CRLM needs to be clarified, in particular for those suffering from early recurrence of CRLM. Methods:. In this multicenter observational cohort study, consecutive patients diagnosed with recurrent CRLM between 2009 and 2019 were retrospectively identified in 4 academic liver surgery centers. Disease-free interval after initial local treatment of CRLM was categorized into recurrence within 6, between 6 and 12, and after 12 months. Perioperative systemic therapy consisted of induction, (neo)adjuvant, or combined regimens. Overall and progression-free survival after repeat local treatment of CRLM were analyzed by multivariable Cox regression analyses, resulting in adjusted hazard ratios (aHRs). Results:. Out of 303 patients included for analysis, 90 patients received perioperative systemic therapy for recurrent CRLM. Favorable overall (aHR, 0.45; 95% confidence interval [CI], 0.26–0.75) and progression-free (aHR, 0.53; 95% CI, 0.35–0.78) survival were observed in patients with a disease-free interval of more than 12 months. No significant difference in overall and progression-free survival was observed in patients receiving perioperative systemic therapy at repeat local treatment of CRLM, stratified for disease-free interval, previous exposure to chemotherapy, and RAS mutation status. Conclusions:. No benefit of perioperative systemic therapy was observed in overall and progression-free survival after repeat local treatment of recurrent CRLM.